Analisis Gaya Kepemimpinan Dalam Meningkatkan Kinerja Pegawai (Study Kasus PT. BPR Prima Nusatama di Bekasi) - Suryati, Suryati; Andari Ratna Widyastuti, Trie (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The aim of this research is to analyze leadership style on employee performance at PT. BPR Prima Nusatama. The research method used is qualitative with a case study approach and data collection techniques through documentation, observation and semi-structured interviews in the interview and library research categories. The informants for this research were HRD, PE Compliance, APU-CFT Risk Management, Head of Marketing, and Collector, and interviewed academics. The research results show that the application of leadership style to the performance of PT employees. BPR Prima Nusatama is quite good, but there are several leaders who have an attitude of not caring about employee performance, such as a lack of attention and guidance when assigning tasks to employees, this is what causes a lack of motivation regarding the quality of employee performance at PT. BPR Prima Nusatama. To improve the quality of employee performance, it starts with oneself, as well as support from the leader.